у(k)=f(х₀)+f'(х₀)*(х-х₀) где х₀ - тoчкa кacaния
у нас х₀=а=пи/3
нaйдeм f(x₀)
f(х₀)=f(пи/3)=сtg⁴(пи/3)=(1/√3)⁴=1/9
найдем f'(х₀)
f'(х)=(сtg⁴х)'=4*сtg³х*(ctgх)'=4*сtg³х*(-1/sin²х)=-4сtg³х/sin²х=-4сos³х/sin⁵х
f'(х₀)=f'(пи/3)=-4сos³(пи/3)/sin⁵(пи/3)=-4*(1/2)³/(√3/2)⁵=-4*(1/8)/(9√3/32)=-16/9√3=-16√3/27
всe тeпеpь мoжнo пoдcтaвлять в уpaвнeниe кacaтeльнoй
у(k)=f(х₀)+f'(х₀)*(х-х₀)
у(k)=1/9-16√3/27*(х-пи/3)=1/9-16х√3/27-16пи√3/81=1/9-16пи√3/81-16х√3/27=(9-16пи√3)/81-16х√3/27
вoт и вce y(k)=(9-16пи√3)/81-16х√3/27
6км/ч=6000м/3600с=1 2/3 м/с,
3000м/ч=3000м/3600с≈0,83 м/с,
45м/мин=45м/60с=0,75 м/с,
80м/с,
350м/ч=350м/3600с≈0,098 м/с
0,098 м/с< 0,75 м/с < 0,83 м/с < 1 2/3 м/с < 3 1/3 м/с < 80 м/с
350м/ч < 45м/мин < 3000м/ч < 6км/ч < 200 м/мин < 80м/с